Recourse and Residential Mortgage Default: Evidence from US States - Ghent, Andra C.; Kudlyak, Marianna (Review of Financial Studies, 2011)
We quantify the effect of recourse on default and find that recourse affects default by lowering the borrower's sensitivity to negative equity. At the mean value of the default option for defaulted loans, borrowers are 30% more likely to default in non-recourse states. Furthermore, for homes appraised at $500,000 to $750,000, borrowers are twice as likely to default in non-recourse states. We also find that defaults are more likely to occur through a lender-friendly procedure, such as a deed in lieu, in states that allow deficiency judgments. We find no evidence that mortgage interest rates are lower in recourse states.